The Effect of Jigsaw Strategy of Cooperative Learning on the Academic Achievement of Five Grade Students in Science Subject - Sultan, Manal; Biraghl, Somar; Assad , Maha (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research aimed to explore the Effect of Jigsaw Strategy of cooperative learning on the Academic Achievement of Five Grade Students in Science Subject, to achieve the research goals a random sample was taken of (80) Students of Five Grade in Lattakia city, (40) of which for the control group and (40) for the experimental group for the academic years: 2017/2018. It was applied on the experimental group learning program, which design according to Jigsaw Strategy, that contain four units of Science book, Academic Achievement test, and the semi-experimental method was used. The research reached the following results: - There was an Effect of using Jigsaw strategy in developing the Academic Achievement of Five Grade Students in Science Subject design according to gain Raito. - There were differences in the mean percent of both the experimental and control groups in the post applying on the test of Academic Achievement in favor of the experimental group’s degrees. - There were differences that have statistical indication in the mean percent of scoring of the Five Grade Students of Basic Teaching (males and females) of the experimental group in post applying on Academic Achievement in favor of the females. - There were differences in the mean percent of scoring between the Students in prior and post test on Academic Achievement in favor of the marks of post applying Students. The research offered several recommendations, the most important is the employment to Jigsaw Strategy in teaching Science Subject by diversify in using the teaching methods.